PENGARUH EKSTRAK DAUN BINTARO (CERBERA ODOLLAM GAERTN) TERHADAP MORTALITAS LALAT RUMAH (MUSCA DOMESTICA LINNAEUS) - Asti Haningtias Sari; Retno Hestiningsih; Sri Yuliawati; Martini Martini (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
House flies are a species that can be found in the environment and play a role in health problems. The use of plant-based insecticide is an alternative to reduce the negative impact of chemical insecticides. One of them is by using bintaro leaf extract. This study aims to determine the effect of giving various concentrations of bintaro leaf extract on the mortality of house flies. This type of research is experimental research design with Posttest Only Control Group Design. The parameter observed was the LC50 mortality of house flies with probit regression analysis. The sample in this study were as many as 1200 adult-stage house flies caught from TPA Jatibarang Semarang The results showed that the LC50 concentration of Bintaro leaf extract was 86%. Based on the one-way Anova test, it is known that p value = 0.001 (p <0.05) means that there is a significant difference between the mortality of flies for each concentration of Bintaro leaf extract From this research it can be concluded that Bintaro leaf extract has the power to kill house flies as adults. Researchers suggest that further research is needed on the use of Bintaro leaf extract using other methods, as well as on other vectors that act as vectors of disease.